Global DNA Methylation Levels in Epstein-Barr-Virus-Positive Iraqi Patients with Acute Lymphoblastic Leukaemia - Lafta, Fadhel M.; AL-Jumaily, Rakad M. Kh; Rasoul, Lubna Muhi (Iraqi Journal of Science, 2023)
Acute lymphoblastic leukemia (ALL) is one of the commonest hematological malignancies affecting children and adults. Recent evidence suggests an involvement of Epstein-Barr virus (EBV) in ALL pathogenicity. Epigenetic aberration, especially altered DNA methylation marks, is a key event of cancer development. The present study aims to investigate how the ALL epimethylome reacts to viral infection through the assessment of the total 5-methylcytosine (5mC) levels in ALL patients, according to EBV infection. The 5mC global DNA methylation levels in 50 diagnosed ALL patients (age mean 26.23 yrs; age range 10-60 yrs) and 25 age-matched healthy controls were assessed using MethylFlash™ Methylated DNA Quantification Kit. Acute primary EBV infection in the studied subjects was detected by measuring Epstein-Barr Virus (EBNA-1) IgG levels using ELISA.     The results showed a significant (P˂0.001) decrease in 5mC levels in ALL-EBV positive cases as compared to those who were negative for EBV infection (0.234±0.117 vs. 0.441±0.153, respectively). The reduction in the average 5mC level seemed to be negatively correlated with EBV viral load (r = -0.599, p= 0.001). Additionally, 5mC levels were able to distinguish between ALL main subtypes (B-ALL and T-ALL; derived from B or T lymphocytes), where T-ALL cases showed significantly (P=0.005) higher 5mC levels than those of B-ALL cases (0.587±0.070 vs. 0.180±0.092, respectively). Also significantly (P=0.04) lower 5mC levels were detected in Philadelphia chromosome-positive (Ph+) ALL cases than in those who were negative to this genetic abnormality (Ph- -ALL) (0.13±0.021 vs. 0.179±0.093, respectively). Overall, the findings of the present study suggest an involvement of EBV infection in ALL pathogenicity, with the potential of utilizing the differences in global DNA methylation levels in ALL patients' risk stratification.